Influencia del tratamiento térmico en productos lácteos - Blas Tello, Raul Helber (2015)
This paper aims to provide information on and analyze recent contributions about the Influence of heat treatment on dairy products. Changes were found in the milk components affected by the heat treatment as in proteins (emulsion properties, α-lactalbumin and β-lactoglobulin), lactose (lactulose formation), enzymes (activity of lactoperoxidase, Υ-glutamyl transferase and alkaline phosphatase), vitamins (vitamin D stability), fat (particle size and stability of linoleic acid), on bacteria (aerobic and bacillus amyloliquefaciens) on microbial agents (tetracycline and sulfonamide), and other variables such as aromatic hydrocarbons (PAHs) and growth factor (TGF-β2); furthermore changes in the physical properties of yogurt (syneresis, roughness, grain number and perimeter) and cheese (proteolysis, lipolysis and sensory characteristics) also affected by the heat treatment is found.